Outcomes of 50 patients entering an adolescent bariatric surgery programme. Issue 12 (9th August 2017) - White, Billy; Doyle, Jacqueline; Matschull, Kirsten; Adamo, Marco; Christie, Deborah; Nicholls, Dasha; Kinra, Sanjay; Wong, Ian Chi Kei; Viner, Russell M
Abstract : Objective: Bariatric surgery is the most effective intervention for weight loss and obesity-related comorbidities currently available. Little is known about adolescents entering National Health Service (NHS) bariatric programmes. We aimed to characterise those entering a pathway and report their outcomes. Design: Prospective service evaluation of patients assessed within a single NHS adolescent bariatric service. Results: 50 patients assessed between 26 July 2007 and 27 January 2014; 6 (12%) were not eligible for surgery, 7 (14%) actively opted out, 8 (16%) were lost to follow-up and 29 (58%) underwent surgery (18 sleeve gastrectomy (SG) 11 Roux-en-y gastric bypass (RYGB) and 0 adjustable gastric band). Mean (SD) age at initial assessment was 16.0 (1.3) years and 18.3 (1.3) at surgery (youngest 15.7 years). Mean time taken to surgery was 1.8 years; longer in those with higher body mass index (BMI) and aged below 14 at first assessment. Mean (SD) BMI at surgery was 53.1 (8.3) kg/m 2, lower in those undergoing RYGB (−5.2, 95% CI −11.6 to 1.13). Follow-up was inconsistent and challenging; 1/29 (3.5%) was transferred to a regional centre, 10/29 (34.5%) attended ongoing follow-up within our protocol, 6/29 (20.7%) had intermittent monitoring and 12/29 (41.4%) were lost to follow-up. Mean BMI change at 1 year (−14.0 kg/m 2 ) and complications were similar to published cohorts. Data from 11 lost to follow-up were obtained and outcomes appeared similar to those who actively followed up. Conclusion: Adolescent bariatric surgery in the NHS appears effective, with outcomes similar to those reported internationally. Further work is needed to optimise postsurgical surveillance and reduce age at surgery.